Kyai Leadership in Promoting Religious Moderation: A Case Study in Indonesian Pesantren - Tohir Muntoha; Idham Kholid; Subandi Subandi; Rumadani Sagala (AL-ISHLAH: Jurnal Pendidikan, 2025)
Pesantren, as traditional Islamic boarding schools in Indonesia, play a strategic role in promoting religious moderation. However, there is a lack of empirical research explicitly linking kyai leadership models to the internalization of moderate Islamic values. This study employed a qualitative case study approach at two pesantren in Tulang Bawang, Lampung. Data were collected through in-depth interviews with 25 participants (kyai, administrators, and senior students), participant observation, and document analysis. Thematic analysis was used to interpret the data. The findings reveal a hybrid transformational-participatory leadership model practiced by the kyai. Transformational aspects include exemplary conduct, inspirational vision, and intellectual stimulation, while participatory elements empower students through structured involvement in decision-making and program implementation. These leadership dynamics are operationalized through three main strategies: (1) contextual interpretation of classical texts (kitab kuning), (2) dialogical preaching and inclusive communication, and (3) experiential learning through interfaith engagement and community immersion. Despite challenges such as radical external influences and the stigma of moderation, kyai leadership has significantly shaped santri mindsets toward tolerance, empathy, and inclusive Islamic identity. This study contributes to the enrichment of transformational leadership theory in religious education and offers practical insights into embedding Wasathiyah Islam through culturally rooted pedagogies. Kyai leadership is central to fostering religious moderation in pesantren. Support from policymakers and curriculum developers is vital to sustaining this leadership model in strengthening inclusive Islamic education.